Can We Reinvent International Studies on Southeast Asia for the Post Western World? - Suzie Sudarman (Indonesian Journal of International Relations, 2017)
Since the end of the Cold War the Asia-Pacific region draws increased attention but there is a gap between the rich comparative and foreign policy scholarship on China, Japan, and the United States with the wider world of international relations theory. Although Pierre Lizee’s work, quoting Stanley Hoffmann, puts forward an argument that international studies as a discipline assumes that it speaks to the nature of politics throughout the entire world,1 it is evident that the study of Southeast Asia in particular, tends to be under-theorized.2 The images, concepts, and theories which underlie international studies as Hoffmann argued, must be recognized for what they are: product of the post-1945 era, when “to study United States foreign policy was to study the international system and to study the international system could not fail to bring one back to the role of the United States.”3